Avaliação de desempenho multicritério em uma instituição de ensino técnico e profissionalizante - Capellin, Fábio (2022)
Despite the development and modernization of management methodologies applied to the educational sector, there is a lack of studies to assess organizational performance in the context of professional and technical education institutions around the world. Therefore, this study aims to build a performance evaluation model to support the strategic and operational management of a technical and vocational education institution. This study is characterized as field research, supported by documental-bibliographic analysis and semi-structured interviews. As technical procedures, the Knowledge Development Process Constructivist (ProKnow-C) is defined as an instrument for systematic literature review, and the Multi-Criteria Decision Aid Constructivist (MCDA-C) methodology as an intervention instrument for the construction of the multicriteria performance evaluation model. For initial data collection, 2 systematic literature reviews were carried out, thus constituting 2 distinct bibliographic portfolios. The bibliographic portfolio 1 is made up of 17 articles and represents the performance evaluation in the context of technical and vocational education institutions. The bibliographic portfolio 2 is composed of 21 articles and presents the main strategic and operational management practices in educational institutions. In general, there was a lack of processes and research that clearly understand the complexities, particularities, and uncertainties of current decision-making contexts. Complementarily, for the construction of the performance evaluation model through the MCDA-C, the actors involved in the process were identified and the context under analysis was labeled. Then, the decision maker presented 81 concerns regarding the assessment context, which were grouped into 5 areas of concern: (i) customer relationship management, (ii) quality management, (iii) financial management, (iv) branding, and (v) administrative management. From the areas of concern and the expansion of knowledge of the decision maker, the concerns of the decision-maker gave rise to action-oriented concepts, which were structured in cause-and-effect relationships and graphically represented in maps of means and ends. This structuring made it possible to organize the concepts in a top-down format, giving rise to a hierarchical values structure. At the end of the hierarchical values structure, 116 descriptors were constructed, represented by ordinal scales that made it possible to evaluate the performance of all possible alternatives individually. Subsequently, the 116 descriptors were transformed into cardinal scales and integrated using compensation rates, identified by applying the Measuring Attractiveness method by a Categorical Based Evaluation Technique (MACBETH). Finally, the process made it possible to identify the impact profile and status quo of the institution, currently at 26.9 points, as well as the development of action plans to improve institutional performance, which would allow the institution to reach 63.7 points. In general, it is highlighted that the process allowed the construction of a unique and relevant performance evaluation model, capable of representing the particularities of the study context, as well as complementing studies found in the literature on performance evaluation in technical and vocational education institutions, with the incorporation of technical and social aspects in a multicriteria model of the constructivist approach.